2013
DOI: 10.3109/00016489.2013.766924
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Swedish version of the Facial Disability Index (FDI) and the Facial Clinimetric Evaluation (FaCE) scale

Abstract: Ninety-three patients were included, 53% women and 47% men, mean age 56.9 years and mean duration of palsy 51.9 months. The questionnaires showed good/excellent psychometric properties with Cronbach's α scores between 0.76 and 0.92. In the test-retest analysis, intra-class correlation coefficients were very good for both questionnaires with scores of 0.83-0.97. Both questionnaires showed good sensitivity to discriminate between patients with varying degrees of facial dysfunction. Moderate to strong correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
52
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 15 publications
12
52
1
Order By: Relevance
“…Twenty‐one studies were found eligible and underwent full‐text appraisal, resulting in nine exclusions. Two studies were a validation study of the FaCE scale in Dutch and Swedish, respectively . One study included the validation of the Synkinesis Assessment Questionnaire .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies were found eligible and underwent full‐text appraisal, resulting in nine exclusions. Two studies were a validation study of the FaCE scale in Dutch and Swedish, respectively . One study included the validation of the Synkinesis Assessment Questionnaire .…”
Section: Resultsmentioning
confidence: 99%
“…The use of the Dutch FaCE Scale can now be implemented in the management of patients with facial palsy in our clinic. With comparable studies in Sweden, China, and Germany, this self-assessment questionnaire for patients with facial palsy is now available in five languages [8, 23, 24, 31]. This is a great step forward in the implementation of a widely used instrument.…”
Section: Resultsmentioning
confidence: 99%
“…The internal consistency of the Dutch FaCE Scale is reflected by a Cronbach’s α of 0.80. The internal consistency of the Swedish and German translations shows a Cronbach’s α of 0.92 and 0.91, respectively [23, 24]. A possible explanation for this difference might be a different patient population used in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey determined that 42% of the membership did not record a structured PROM. One explanation may be that, of an international membership, many of the validated PROMs are in English and may have limited value or require revalidation in another language . Roughly one‐third of those polled used the FaCE scale, and the remainder used the Facial Disability Index (12%) or another method.…”
Section: Discussionmentioning
confidence: 99%